2017
DOI: 10.1016/j.apsb.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Flavanols from the Camellia sinensis var. assamica and their hypoglycemic and hypolipidemic activities

Abstract: α-Glucosidase and lipase inhibitors play important roles in the treatment of hyperglycaemia and dyslipidemia. To identify novel naturally occurring inhibitors, a bioactivity-guided phytochemical research was performed on the pu-erh tea. One new flavanol, named (–)-epicatechin-3-O-(Z)-coumarate (1), and 16 known analogs (2—17) were isolated from the aqueous extract of the pu-erh tea. Their structures were determined by spectroscopic and chemical methods. Furthermore, the water extract of pu-erh tea and its frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…This finding provides evidence that polyphenols in the tea extract are the predominant source of the radical scavenging activities of these tea, which is likely exerted through donation of a hydrogen or electron transfer from the phenolic structure to the radicals (Adjimani and Asare, 2015). Previous studies reported this property comes from polyphenols such as epichatechin, epichatechin galate (Kristanti and Punbusayakul, 2008), and especially epigallochatechin gallate (Wang et al, 2017) which is a catechin derivate possessing eight free hydroxyl groups, thus explaining high antioxidant activity.…”
Section: Discussionmentioning
confidence: 63%
“…This finding provides evidence that polyphenols in the tea extract are the predominant source of the radical scavenging activities of these tea, which is likely exerted through donation of a hydrogen or electron transfer from the phenolic structure to the radicals (Adjimani and Asare, 2015). Previous studies reported this property comes from polyphenols such as epichatechin, epichatechin galate (Kristanti and Punbusayakul, 2008), and especially epigallochatechin gallate (Wang et al, 2017) which is a catechin derivate possessing eight free hydroxyl groups, thus explaining high antioxidant activity.…”
Section: Discussionmentioning
confidence: 63%
“…In a similar work, Xu et al (2014) [38] found that pu-erh tea polysaccharides with aging for 3 years and 5 years resulted in inhibition of α-glucosidase enzyme activity with same potency as acarbose (3 years aging) and three times more potently than acarbose (5 years aging). Besides, water extract of pu-erh tea moderately inhibited sucrose activity (IC 50 = 14.4 µg/mL) and maltase (IC 50 = 11.4 µg/mL), the compound epigallo-catechin-3-O-gallate having the greatest inhibitory activity with IC 50 = 32.5 µM against sucrose and IC 50 = 1.3 µM against maltase [14]. In another study, the ethyl acetate fraction from Qingzhuan tea extracts showed significant α-glucosidase inhibitory potential (IC 50 = 0.26 µg/mL), attributing this activity to the compounds epigallocatechin gallate and epicatechin gallate.…”
Section: Camellia Sinensis and Diabetesmentioning
confidence: 99%
“…Particularly, diabetes was the most study disease in in vitro studies (n = 16) and obesity in in vivo studies (n = 20), and clinical trials (n = 6). In several in vitro and in vivo studies, the effect of extracts and isolated compounds of Camellia sinensis on two different pathologies were studied in the same research work [9][10][11][12][13][14][15][16]. This review is divided into six sections, based on the pathologies, diabetes, hypercholesterolemia, hypertension, metabolic syndrome, obesity, and osteoporosis.…”
Section: Pharmacological Activity Description Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that avanols from the water extract of pu-erh tea showed an inhibition effect on aglucosidase, suggesting potential hypoglycemic effects. 6 In the study of Deng et al, a single administration of polysaccharides from pu-erh tea decreased the postprandial blood sugar in mice, and the mechanism was due to the inhibition of a-glucosidase. 7 Huang et al reported that the 95% ethanol precipitate and ethyl acetate fractions of pu-erh tea showed remarkable inhibition against a-glycosidase in vitro.…”
Section: Introductionmentioning
confidence: 99%